1991
DOI: 10.1007/bf01986590
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic activity of a novel bivalent opioid peptide compared to morphine via different routes of administration

Abstract: A novel bivalent opioid tetrapeptide, biphalin (Tyr-D-Ala-Gly-Phe-NH)2, was synthesized based on structure-activity relationships. The analgesic activity of biphalin was assessed in comparison to morphine in rats. Drugs were administered subcutaneously (s.c.), intravenously (i.v.) and intrathecally (i.t.). Tail flick and tail pinch were used as tests for analgesia. Biphalin s.c. showed negligible analgesic activity, but when given i.v. produced significant analgesia, although less potent than morphine via this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…This peptide also produces antinociceptive effects comparable with morphine after systemic injection and has been shown to produce less dependence than morphine on chronic use. 50,51 Similarly to biphalin, it seems that modulating frequency exerts a dual agonist action at μ-and δ-opioid receptors which has been shown to cause a delay in the development of tolerance to TENS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide also produces antinociceptive effects comparable with morphine after systemic injection and has been shown to produce less dependence than morphine on chronic use. 50,51 Similarly to biphalin, it seems that modulating frequency exerts a dual agonist action at μ-and δ-opioid receptors which has been shown to cause a delay in the development of tolerance to TENS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that biphalin has high affinity to mu opioid receptor (MOP) and delta opioid receptor (DOP) but lower affinity to kappa opioid receptor (KOP) [11, 12]. An antinociceptive character of biphalin was documented in an animal model of cancer pain [13], a semichronic colitis model [14], and in naïve animals [15, 16]. Biphalin exhibits 1000-fold greater analgesic potency than morphine [17, 18] and produces less side effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several other analgesics are also available with similar potencies for which similar calculations could be made. As with hydromorphone, the drugs listed below may be delivered intramuscularly (IM) or subcutaneously (SC) (PDR, 1994;Beaver, 1980 It is to be noted that recent work with opioid peptides (Silbert et al, 1991;Misterek, 1994) indicates that these are also highly potent analgesics. On the other hand, the choice of hydromorphone for this study was based on several considerations.…”
Section: Phase I Statement Of Workmentioning
confidence: 99%
“…Measurements were taken prior to implantation to establish base line data and following implantation at 0.5 hrs, and subsequently at days 2, 4, 7, and 8 or 9. The percent of maximum analgesic response (% MAR) was calculated from the following equation (Silbert et al, 1991).…”
Section: In Vivo Testingmentioning
confidence: 99%